RASHDU FADLA-AT HETEROTOPIA FI QISHAT “SYAHINAT BARLIN” AL-QASHIRAT LI HASSAN BLASIM - Faizul Munir; M. Dasrul Jabir (Afshaha: Jurnal Bahasa dan Sastra Arab, 2024)
Syahinat Barlin tells the story of the illegal smuggling of 35 immigrants from Turkey to Berlin, packed into a truck. The narrative grippingly reveals the horror of the journey, culminating in the extinction of all but one on board. Blasim carefully uses Gothic techniques to bring readers closer to his characters. While previous analyzes have emphasized Blasim’s gothic narrative, this research highlights the important role of the spatial dimension. In Syahinat Barlin the truck itself, specifically the cargo box, serves as the focal space. According to Foucault, this space transcends binary categorization, embodying a ‘heterotopia’, a reflection of power structures and an alternative to social norms. This research aims to dig deeper into the heterotopic spaces in Syahinat Barlin with a descriptive-qualitative approach and hermeneutic reading. The findings reveal the truck symbolizes three different spaces: a space of deviation, a space of demarcation, and a dark space. Illegal immigrants, who attempted to enter without documents, were treated as deviants, necessitating their isolation in trucks. The truck’s position is at odds with conventional transportation, depicting immigrants as ‘other’. Viewed as deviants, they are monitored and treated as contaminants. Simultaneously, the Berlin truck, functioning as a hidden heterotopia, challenges the moral norms of migration, creating the illusion of utopia as compensation for the harsh reality.